2014
DOI: 10.1093/dnares/dst055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of the Closely Related Synechocystis Strains PCC 6714 and PCC 6803

Abstract: Synechocystis sp. PCC 6803 is the most popular cyanobacterial model for prokaryotic photosynthesis and for metabolic engineering to produce biofuels. Genomic and transcriptomic comparisons between closely related bacteria are powerful approaches to infer insights into their metabolic potentials and regulatory networks. To enable a comparative approach, we generated the draft genome sequence of Synechocystis sp. PCC 6714, a closely related strain of 6803 (16S rDNA identity 99.4%) that also is amenable to geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 51 publications
6
67
0
Order By: Relevance
“…Using BlastN, putative nsiR4 homologs were identified in at least 38 additional genomes, including the closely related Synechocystis sp. PCC 6714 (hereafter referred to as Synechocystis 6714) (32,33), more distantly related strains, such as Synechococcus sp. PCC 7002, or several Anabaena and Nostoc species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using BlastN, putative nsiR4 homologs were identified in at least 38 additional genomes, including the closely related Synechocystis sp. PCC 6714 (hereafter referred to as Synechocystis 6714) (32,33), more distantly related strains, such as Synechococcus sp. PCC 7002, or several Anabaena and Nostoc species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCC6803 was sequenced in 1996 [37][38][39][40], allowing identification of genes responsible for the natural production of PHA in cyanobacteria. In contrast, genomic data of Synechocystis cf.…”
Section: Isolation Of Phaa-b Syn6909 and Phae-c Syn6909 Gene Clustersmentioning
confidence: 99%
“…PCC 6714 that is closely related to PCC 6803. 48 They showed that the 16S rRNA-coding segment is 99.4% identical to that of PCC 6803, but that almost a quarter of protein-coding genes is unique to each strain.…”
Section: 10 Synechocystis Sp Pcc 6803mentioning
confidence: 99%